2013
DOI: 10.1007/s12262-013-0820-9
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Jejunojejunal Intussusception

Abstract: Intussusception is a well-known cause of acute abdomen in the pediatric population. Traumatic intussusception is exceedingly rare, with only 22 cases reported in the English language literature. We report a case of jejunojejunal intussusception that happened after blunt trauma to the abdomen in a 10-year-old boy. The patient presented with clinical presentation of small-bowel obstruction. Through this case and brief review of the literature, we try to focus on the etiology of this rare condition, the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…From 1925 to 2021, 28 cases have been reported in the literature. Only 12 cases described pediatric patients younger than 15 years of age ( Table 1 ) [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] . Of these 12 cases, 11 cases discussed small bowel intussusception and one case discussed ileocolic intussusception [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From 1925 to 2021, 28 cases have been reported in the literature. Only 12 cases described pediatric patients younger than 15 years of age ( Table 1 ) [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] . Of these 12 cases, 11 cases discussed small bowel intussusception and one case discussed ileocolic intussusception [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Since multiple traumatic intussusceptions are very rare in children, the mechanisms of their emergence are not clearly understood. Some proposed mechanisms include local intestinal spasm or edema following pathologic peristalsis, sympathetic hyperactivation, or intramural hematoma after trauma [9] , [10] . Since the patient in our case had no bowel wall edema or intramural hematoma, we hypothesized that the possible cause of multiple intussusceptions might be sympathetic hyperactivation leading to localized intestinal spasm or pathologic peristalsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manual surgical reduction without resection of bowel is sufficient, if there is no evidence of bowel ischemia or concern for malignancy. 1 In conclusion, although intussusception in the trauma setting is rare, it may be a cause of postoperative bowel obstruction after a trauma laparotomy, and surgical intervention is strongly advised.…”
Section: Intussusception Caused By a Mesenteric Hematoma In The Setting Of Traumamentioning
confidence: 95%
“…Intussusception in the setting of trauma is very rare, with literature quoting only 22 case reports in the English language literature since 2012. 1,2 In published studies, abdominal trauma was found as the etiological factor in only 0.7 to 1.96 per cent of all adults having intussusception. 3 Mesenteric hematomas occur because of the surrounding mesenteric injury caused by blunt trauma, and if the hematoma is nonexpanding and contained, it can often be left alone.…”
Section: Intussusception Caused By a Mesenteric Hematoma In The Setting Of Traumamentioning
confidence: 99%